P150 Use of ambulatory oxygen therapy in pulmonary rehabilitation. (2nd December 2011) - Anderson, D; Valls, S Ferrer; Church, S; Agarwal, S
Abstract : Introduction and Objectives: Pulmonary rehabilitation (PR) is proven to improve oxygen exercise capacity, health status and reduce dyspnoea in patients diagnosed with Chronic Obstructive Pulmonary Disease. Previous studies have shown no significant difference in rehabilitation outcomes following use of supplemental oxygen during pulmonary rehabilitation. Unfortunately, a few patients are unable to exercise due to hypoxia related dyspnoea depriving them of the benefit of PR. We hypothesised that the use of Ambulatory Oxygen Therapy (AOT) in patients with exercise induced desaturation would increase their capability of undergoing PR and have an overall positive outcome. Methods: Requirement of AOT is routinely assessed at our trust prior to commencing PR. Incremental oxygen is used to decide on the flow rate needed during PR. A retrospective study was performed to evaluate the benefits of AOT in patients desaturating on exertion. Data were analysed using Excel. Results: 218 patients were enrolled for the programme from January 2009 to July 2010, 46 excluded as not suitable or did not attend. Numbers studied-172: 59% male, mean age 70 (range 45–90), 25% current smokers. On initial endurance exercise test 27% (n=47) were noted to have exercise induced desaturation. Seven patients were already on long-term oxygen therapy. Median prescribed flow rate was 2 l/min during PR. The mean distance walked on initial endurance test was 150 m. This improved significantly to 263 m (p<0001) with AOT. 68 % (n=32) attended for post PR endurance exercise testing, 25% no longer required AOT (did not desaturate). Of the 22 patients (46%) who continued to require AOT, 14 were prescribed. Following 2 months of the prescription, AOT was withdrawn in four patients as they found the cylinder too heavy or did not benefit. Conclusions: AOT has shown significant improvement in rehabilitation outcomes in patients with exercise induced desaturation. A quarter of these patients did not require any further ambulatory oxygen therapy following pulmonary rehabilitation.